Changes In The Cultural Practices Of The Thengal Kachari Tribe Of Assam –A Study - Suravi Gohain Duwarah (Elementary Education Online, 2023)
Change is inevitable in a society. Change in culture is a universal phenomenon and cultural change occur due to many factors and reasons. Transformation or change is a continuos process and this process differs from society to society. In some society transformation in culture may take place very rapidly and in some it becomes very slow. Thus it may be said that the process of change is not the same everywhere.